PERAN KECERDASAN BUATAN TERHADAP TRANSFORMASI PENDIDIKAN DI ERA DIGITAL - M. Nasihuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study explores the role of Artificial Intelligence (AI) in transforming education in the digital era. The main issue addressed is how AI enhances learning effectiveness and educational administration while facing challenges in its implementation. The research method used is a literature review with data analysis from various relevant sources. Data was collected from books, journals, and scholarly articles related to educational transformation, AI, and the digital era. The findings indicate that AI contributes to personalized learning, automated assessment, and data-driven educational management. However, its implementation faces challenges in infrastructure readiness, educator competence, and policy regulations. In conclusion, AI has great potential in education but requires a well-planned implementation strategy to ensure its benefits are optimized inclusively and sustainably.